The Management and Status of Minor Ailments in Community Pharmacies in Central Indonesia: A Mixed Methods Study - Mizranita, Vinci (Curtin University, 2022)
Community pharmacy has an important role in the management of minor ailments in primary care. This study evaluated the management of minor ailments in community pharmacies in Central Java, Indonesia. Discordant perceptions were evident between pharmacists’ and pharmacy technicians’ scopes of practice for minor ailments, leading to potential safety issues for the public. Pharmacy teaching institutions and professional bodies in Indonesia should develop guidelines for managing minor ailments aligned with defined scopes of practice.